In the Footsteps of Food Left by Our Ancestors: “Sowing the Past, Cultivating the Present in Harmony with Mother Earth” - Leiva Morales, Oscar; Díaz Leiva, Rigoberto (Revista Electrónica Educare, 2013)
Indigenous peoples have experienced food shortages in recent years. The rapid destruction of natural resources, lack of incentives for producers, globalization and free tradeagreements havec caused an uprooting from the land in the native mind. Moreover, it has been difficult to establish an adequate relationship between traditional farming practices and technical advice to put the community economy on the right track with new ways to strengthen the knowledge inherited from our grandparents on the cultivation and consumption of agricultural products, in harmony with nature. This reality, which affects the Boruca indigenous region, has led to economic, social and cultural problems, coupled with an evident threat: loss of food sovereignty.